Students Engagement through Gamification in Education Gamifying Formative Assessment - Mishra, Richa; Kotecha, Ketan (Journal of Engineering Education Transformations, 2025)
The web 2.0 has created a singularity effect in the life we lead. The communication and its dissemination; information gathering and its transference; knowledge acquisition and its application ( Mishra and Kotecha) have all been changed in front of us, with us and by us.